Antiperiodic Boundary Value Problems for Finite Dimensional Differential Systems. (29th June 2009) - Chen, Y. Q.; O'Regan, D.; Wang, F. L.; Zhou, S. L.
Abstract : We study antiperiodic boundary value problems for semilinear differential and impulsive differential equations in finite dimensional spaces. Several new existence results are obtained.